2001
DOI: 10.1668/0003-1569(2001)041[1078:oooict]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Ontogeny of Osmoregulation in Crustaceans: The Embryonic Phase1

Abstract: SYNOPSIS. Following a brief overview of the patterns of ontogeny of osmoregulation in postembryonic stages, this review concentrates on the ontogeny of osmoregulation during the embryonic development of crustaceans, particularly in those species living under variable or extreme salinity conditions and whose hatchlings osmoregulate at hatch. Two situations are considered, internal development of the embryos in closed incubating, brood or marsupial pouches, and external development in eggs exposed to the externa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(8 citation statements)
references
References 54 publications
1
7
0
Order By: Relevance
“…The present study shows that G. aequicauda can survive and grow in a wide range of salinities between 2 psu and 40 psu. These values are similar to those reported in other euryhaline peracarida species, such as the isopod Sphaeroma serratum Fabricius [37], the tanaidacea Tanais cavolinii Milne-Edwards [38] and the amphipods Hyale crassicornis Haswell [39], Traskorchestia traskiana Stimpson [40], Orchesia gammarellus Pallas [41], Orchesia chiliensis Milne-Edwards [42], Cyathura polita Stimpson [6,43] and G. duebeni Lillgeborg [44].…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The present study shows that G. aequicauda can survive and grow in a wide range of salinities between 2 psu and 40 psu. These values are similar to those reported in other euryhaline peracarida species, such as the isopod Sphaeroma serratum Fabricius [37], the tanaidacea Tanais cavolinii Milne-Edwards [38] and the amphipods Hyale crassicornis Haswell [39], Traskorchestia traskiana Stimpson [40], Orchesia gammarellus Pallas [41], Orchesia chiliensis Milne-Edwards [42], Cyathura polita Stimpson [6,43] and G. duebeni Lillgeborg [44].…”
Section: Discussionsupporting
confidence: 86%
“…Previous studies on the biology and population dynamics in the Ebro delta showed that abundance is not correlated with changes in salinity [13]. Researchers argue about the ontogenetic variations in the osmoregulatory ability in some species of amphipods [6,[29][30][31][32], whereas in G. aequicauda, the salinity conditions in which embryos and juveniles can survive and develop are currently unknown.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The high mortality we observed in the 0 mg l −1 calcium treatment could be related to the onset of direct environmental calcium interaction with newly formed osmoregulatory organs after hatching the vitelline membrane (Charmantier and Charmantier-Daures, 2001). It is likely that the embryonic calcium resources of D. magna are exhausted by stage 5, and must be supplemented with environmental calcium.…”
Section: Influence Of Environmental Calcium On Embryogenesis and Embrmentioning
confidence: 83%
“…If the embryonic membranes of D. magna are involved in early embryonic osmoregulation (Charmantier and Charmantier-Daures, 2001), and the transfer of larger minerals such as calcium across these membranes is regulated by complex transport mechanisms as seen in, for example, the chick embryo (Tuan and Ono, 1986), bioassays that employ simple pharmacological exposures may not demonstrate the true effects of the disruptive compounds on embryos if the compounds are unable to cross these barriers. Properly incorporating compounds into the embryos might require acclimating mothers to the compound, and having them transfer it naturally to the embryos as seen with calcium.…”
Section: Influence Of Environmental Calcium On Embryogenesis and Embrmentioning
confidence: 99%